Speaking in ink: Verbal and nonverbal communication as identity construction in an Indonesian tattoo subculture community - R. Muhammad Ihsan; Irna Hardiyanti; Elyusra Elyusra (Privietlab, 2026)
Communication within special interest communities operates through layered systems of meaning that extend well beyond the simple exchange of information. This study examines the verbal and nonverbal communication patterns of the Purwokerto Tattoo Club (PTC), a formally organized tattoo subculture community based in Purwokerto, Central Java, Indonesia, active since 2010. Employing a qualitative ethnographic approach, data were collected between January and March 2025 through participatory observation, in-depth interviews, and documentation involving three categories of informants: active tattooists, registered tattoo enthusiasts, and community administrators. Informants were selected through purposive sampling, and data validity was ensured through source and method triangulation. Findings reveal that the PTC community has developed an integrated communicative ecosystem in which verbal and nonverbal dimensions operate synergistically. In the verbal dimension, WhatsApp Group functions as a digital social space sustaining real-time coordination and community solidarity, while a system of technical jargon, comprising the terms performing, gangbang tattoo, and colouring, serves as a linguistic identity marker distinguishing members from the broader social world. In the nonverbal dimension, physical appearance through tattoos and piercings, vocalics, artifacts, haptics, and color symbolism collectively construct the community's collective identity and social cohesion. These findings affirm that subcultural community communication cannot be studied in isolation but requires an integrative analytical framework. This study contributes a new perspective on special interest community communication in the Southeast Asian context, where such research remains largely underrepresented in the academic literature.